The Influence of Menthol in Ethanol Extract of Meniran Gel (Phyllanthus niruri L.) as a Hair Growth Promoter in Male Wistar Rats - Sri Luliana; Rise Desnita; Utia Mufliha (Majalah Obat Tradisional, 2019)
Phyllanthus niruri L. is known to promote hair growth. Menthol is one of the enhancers which promotes drug penetration into the skin. The aim of this research is to determine the potential of menthol in P. niruri Ethanol Extracts gel preparation as a hair growth promoter. The test animals were randomized into 4 groups: normal group, negative control (gel without extract and menthol), E1 group (Ethanol Extracts of P. niruri 5% gel without menthol) and E2 group (Ethanol Extracts of P. niruri 5% gel with menthol). Hair growth activity test was conducted by applying the gel on the rats’ back, and hair length was measured on the 7th, 14th and 21st days, while the hair was weighed on the 21st day. The results showed that the E2 group had an average hair length and hair weight of 12.45±3.457 mm and hair weight of 28.53±7.681 mg, greater than the E1 group of 10.67±2.455 mm and 19.87±9.552 mg respectively. Based on these results, it can be concluded that adding menthol in P. niruri Ethanol Extract gel preparation can influence hair growth and thickness.